(E)-2,4-Dihydroxy-N′-(2-hydroxy-3-methoxy-5-nitrobenzylidene)benzohydrazide dihydrate - Han, You-Yue (International Union of Crystallography, 2010)
The asymmetric unit of the title compound, C(15)H(13)N(3)O(7)·2H(2)O, consists of a hydrazone molecule and two solvent water molecules. The molecule adopts an E configuration with respect to the C=N bond. It is relatively planar, with a dihedral angle between the two benzene rings of 2.6 (1)°. There are intramolecular O—H⋯N and O—H⋯O hydrogen bonds in the hydrazone molecule. In the crystal structure, symmetry-related molecules are linked through intermolecular N—H⋯O and O—H⋯O hydrogen bonds to form a three-dimensional network.